External marker in bisecting-angle-technique: a new approach to minimize dental radiographic error - Azizah Ahmad Fauzi; Muhamad Aqil AA; Mohd Amirul Z; Atika A (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Bisecting-angle-technique is a method used to improve patient comfort during periapical radiography. This technique is usually performed without X-ray beam aiming device and has been commonly associated with dental radiographic error. The use of external marker as a beam aiming device in bisecting-angle-technique is potentially effective to reduce the number of errors occurring during periapical radiography. In this study, 240 periapical radiographs were taken by undergraduate dental students. Periapical radiographs were taken using traditional method of bisecting-angle-technique (BAT), bisecting-angle-technique with the use of external marker (BAT-M) and the standard method in periapical radiography; paralleling technique (PT). All radiographic images were evaluated and errors were classified and tabled according to the type and number of errors. Chi-square test was used to compare the total number of radiographic errors made using these three techniques. One of the most common errors with BAT was cone cut error (13.8%). This error had been markedly reduced to 1.3% and 2.5% by implementation of BAT-M and PT, respectively. The total number of errors was also found to be significantly lesser for BAT-M compared to BAT, p< 0.05.